INTEGRATING MIND, BODY, AND RESILIENCE UNDERSTANDING MEDIATING FUNCTION OF BODY AWARENESS IN ADOLESCENT ATHLETES’ MENTAL TOUGHNESS - Hana Fatmawati; Miftakhul Jannah (HEALTHY : Jurnal Inovasi Riset Ilmu Kesehatan, 2026)
ABSTRACT The development of adolescent athletes has predominantly focused on technical skills and performance, while psychological and somatic dimensions such as body awareness have received limited attention. This study aims to examine the mediating role of body awareness in the relationship between sense of mastery and mental toughness among adolescent athletes. A quantitative approach with a survey method was employed, involving 113 adolescent athletes from various sports at a specialized sports school in Indonesia. Data were collected using questionnaires and analyzed using mediation regression analysis (MRA) to examine both direct and indirect effects among variables. The findings indicate that sense of mastery has a positive effect on mental toughness, and body awareness functions as a significant mediator in this relationship. These results suggest that higher levels of sense of mastery are associated with increased body awareness, which in turn contributes to enhanced mental toughness. Therefore, the study highlights that integrating body awareness training into adolescent athlete development programs has the potential to improve mental toughness in a more comprehensive manner. ABSTRAK Perkembangan atlet remaja saat ini masih cenderung berfokus pada aspek teknis dan performa, sementara dimensi psikologis dan somatik seperti kesadaran tubuh belum mendapat perhatian optimal. Penelitian ini bertujuan untuk menganalisis peran mediasi kesadaran tubuh dalam hubungan antara sense of mastery dan mental toughness pada atlet remaja. Penelitian menggunakan pendekatan kuantitatif dengan metode survei terhadap 113 atlet remaja dari berbagai cabang olahraga di salah satu sekolah khusus olahraga di Indonesia. Pengumpulan data dilakukan menggunakan instrumen kuesioner, kemudian dianalisis dengan analisis regresi mediasi (MRA) untuk menguji pengaruh langsung dan tidak langsung antar variabel. Hasil penelitian menunjukkan bahwa sense of mastery berpengaruh positif terhadap mental toughness, serta kesadaran tubuh berfungsi sebagai mediator signifikan dalam hubungan tersebut. Temuan ini mengindikasikan bahwa peningkatan sense of mastery berkaitan dengan meningkatnya kesadaran tubuh, yang selanjutnya berkontribusi pada penguatan mental toughness. Dengan demikian, penelitian ini menunjukkan bahwa integrasi latihan kesadaran tubuh dalam program pembinaan atlet remaja berpotensi meningkatkan ketangguhan mental secara lebih komprehensif.